Water stress detection in the Amazon using radar. Issue 13 (13th July 2017) - van Emmerik, Tim; Steele‐Dunne, Susan; Paget, Aaron; Oliveira, Rafael S.; Bittencourt, Paulo R. L.; Barros, Fernanda de V.; van de Giesen, Nick
Abstract: The Amazon rainforest plays an important role in the global water and carbon cycle, and though it is predicted to continue drying in the future, the effect of drought remains uncertain. Developments in remote sensing missions now facilitate large‐scale observations. The RapidScat scatterometer ( K u band) mounted on the International Space Station observes the Earth in a non‐Sun‐synchronous orbit, which allows for studying changes in the diurnal cycle of radar backscatter over the Amazon. Diurnal cycles in backscatter are significantly affected by the state of the canopy, especially during periods of increased water stress. We use RapidScat backscatter time series and water deficit measurements from dendrometers in 20 trees during a 9 month period to relate variations in backscatter to increased tree water deficit. Morning radar bacskcatter dropped significantly with increased tree water deficit measured with dendrometers. This provides unique observational evidence that demonstrates the sensitivity of radar backscatter to vegetation water stress, highlighting the potential of drought detection and monitoring using radar. Key Points: Simultaneous ground measurements of tree water status and RapidScat backscatter Diurnal variation in backscatter differs during wet and dry seasons Radar backscatter is sensitive to tree water stress in Amazon